Mutations and mechanisms in congenital and age-related cataracts. (March 2017) - Shiels, Alan; Hejtmancik, J. Fielding
Abstract: The crystalline lens plays an important role in the refractive vision of vertebrates by facilitating variable fine focusing of light onto the retina. Loss of lens transparency, or cataract, is a frequently acquired cause of visual impairment in adults and may also present during childhood. Genetic studies have identified mutations in over 30 causative genes for congenital or other early-onset forms of cataract as well as several gene variants associated with age-related cataract. However, the pathogenic mechanisms resulting from genetic determinants of cataract are only just beginning to be understood. Here, we briefly summarize current concepts pointing to differences in the molecular mechanisms underlying congenital and age-related forms of cataract.